Peran Moderasi Beragama dalam Membangun Karakter Humanis Gen Z SMA Sint Louis Semarang - Nona Theresia Distress Retang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Religious moderation is an essential approach to shaping the humanistic character of Generation Z (Gen Z) students, particularly in Indonesia’s religious diversity context. This study aims to analyze the level of understanding among teachers and students regarding religious moderation, evaluate the implementation of related programs at SMA Sint Louis Semarang, and identify challenges and solutions for its application. A mixed method of literature review and surveys involving 21 teachers and 137 students was employed. The findings reveal that most teachers (71.4%) and students (45.3%) demonstrate a solid understanding of religious moderation, although some students struggled to articulate its concept. School programs such as interfaith dialogues, visits to places of worship, and project-based learning (PBL) have proven effective in fostering tolerance, empathy, and social harmony among students. However, challenges such as stereotypes, prejudice among students, and reported acts of intolerance (37.2% of students) indicate the need to strengthen character education. This study recommends additional training for teachers, the development of diversity-based programs, and enhanced interfaith dialogues to promote religious moderation in schools. With these strategic steps, SMA Sint Louis Semarang can lead in cultivating a generation that is tolerant, humanistic, and inclusive.